The Process of Democratization in Nepal: Challenges and Possibilities: नेपाल में लोकतंत्रीकरण की प्रक्रिया: चुनौतियाँ और संभावनाएँ - Sharma, Rakesh Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The story of the arrival and consolidation of democracy in Nepal is nothing short of a cinematic script. How a small Himalayan country, which remained under kings and authoritarian rule for centuries, transformed into a modern republic is remarkable. This process began in 1951 with the end of the Rana regime, but the people had to wait several more decades for genuine democracy. After the king crushed democracy in 1960, the popular movements of 1990 and again in 2006 proved that the people of Nepal were no longer willing to bow down. The 2006 movement, in particular, was the most decisive. It not only curtailed the powers of the monarchy but also compelled the Maoist rebels to abandon the path of armed conflict and come to the negotiating table in parliament. The main focus of this research is the new Constitution promulgated in 2015. This constitution marked a new dawn for Nepal, restructuring the country into seven provinces and adopting a federal system. However, merely drafting a constitution does not guarantee the success of democracy. Nepal continues to face several major challenges today. Political instability persists, governments change frequently, and corruption remains a significant problem. Furthermore, safeguarding national interests between powerful neighbors such as India and China presents a critical test for Nepalese democracy. Abstract in Hindi Langauge: नेपाल में लोकतंत्र के आने और जमने की कहानी किसी फिल्मी पटकथा से कम नहीं है। कैसे एक छोटा सा हिमालयी देश, जो सदियों तक राजाओं और तानाशाही के अधीन रहा, आज एक आधुनिक गणराज्य बन गया है। इस प्रक्रिया की शुरुआत 1951 में हुई जब राणा शासन का अंत हुआ, लेकिन असली लोकतंत्र के लिए जनता को कई दशकों तक इंतजार करना पड़ा। 1960 में राजा द्वारा लोकतंत्र को कुचलने के बाद, 1990 और फिर 2006 के जनआंदोलनों ने यह साबित कर दिया कि नेपाल की जनता अब और झुकने को तैयार नहीं है। विशेष रूप से 2006 का आंदोलन सबसे निर्णायक रहा, जिसने न केवल राजा की शक्तियों को खत्म किया, बल्कि माओवादी विद्रोहियों को भी युद्ध का रास्ता छोड़कर संसद की मेज पर आने के लिए मजबूर किया। इस शोध का मुख्य हिस्सा 2015 में बने नए संविधान पर केंद्रित है। यह संविधान नेपाल के लिए एक नई सुबह की तरह था, जिसने देश को सात प्रांतों में बांटकर ’संघीय ढांचा’ अपनाया। हालांकि, केवल संविधान लिख देने भर से लोकतंत्र सफल नहीं हो जाता। नेपाल आज भी कई बड़ी चुनौतियों से जूझ रहा है। यहाँ की राजनीति में अस्थिरता है, सरकारें बहुत जल्दी बदल जाती हैं और भ्रष्टाचार एक बड़ी समस्या बनी हुई है। इसके अलावा, भारत और चीन जैसे बड़े पड़ोसियों के बीच अपने हितों की रक्षा करना भी नेपाली लोकतंत्र के लिए एक अग्निपरीक्षा जैसा है। Keywords: नेपाल, लोकतंत्रीकरण, संघीयता, 2015 का संविधान, राजशाही, माओवादी विद्रोह, समावेशिता, जनआंदोलन।